Asiaticoside, a component of Centella asiatica attenuates RANKL‐induced osteoclastogenesis via NFATc1 and NF‐κB signaling pathways. Issue 4 (26th August 2018) - He, Lilei; Hong, Guoju; Zhou, Lin; Zhang, Jianguo; Fang, Jian; He, Wei; Tickner, Jennifer; Han, Xiaorui; Zhao, Lilian; Xu, Jiake
Abstract : Identification of natural compounds that inhibit osteoclastogenesis will facilitate the development of antiresorptive treatment of osteolytic bone diseases. Asiaticoside is a triterpenoid derivative isolated from Centella asiatica, which exhibits varying biological effects like angiogenesis, anti‐inflammation, wound healing, and osteogenic differentiation. However, its role in osteoclastogenesis remains unknown. Here, we show that Asiaticoside can suppress RANKL‐induced osteoclast formation and bone resorption in a dose‐dependent manner. Asiaticoside attenuated the expression of osteoclast marker genes including Ctsk, Atp6v0d2, Nfatc1, Acp5, and Dc‐stamp . Furthermore, Asiaticoside inhibited RANKL‐mediated NF‐κB and NFATc1 activities, and RANKL‐induced calcium oscillation. Collectively, this study demonstrates that Asiaticoside inhibited osteoclast formation and function through attenuating RANKL‐induced key signaling pathways, which may indicate that Asiaticoside is a potential antiresorptive agent against osteoclast‐related osteolytic bone diseases. Abstract : Asiaticoside can suppress RANKL‐induced osteoclast formation and bone resorption in a dose‐dependent manner. Asiaticoside attenuated the expression of osteoclast marker genes including Ctsk, V‐ATPase d2, NFATc1, TRAcP, and DC‐STAMP . Furthermore, Asiaticoside inhibited RANKL‐mediated NF‐κB and NFATc1 activities, and RANKL‐induced calcium oscillation.